EFEKTIVITAS DAUN KATUK (SAUROPUS ANDROGYNUS) TERHADAP KECUKUPAN ASI PADA IBU MENYUSUI DIMASA PANDEMI COVID-19 - Kristin Natalia (JURNAL ILMIAH DHDT - KEBIDANAN, 2021)
One of the inhibiting factors for stopping breastfeeding is insufficient milk production. The Ministry of Health's Data and Information Center in 2017 stated that only 35% of mothers provide exclusive breastfeeding in Indonesia. 50% of this figure is far below the recommendation of the WHO (World Health Organization). This is due to lack of family support, low knowledge of mothers and less food intake of nursing mothers. Breast milk really helps strengthen the immune system or immunity of babies, especially during the current Covid-19 pandemic. The current impact of Covid-19 has made the people's economy decline, many are unemployed. This results in the lack of adequate milk and the mother becomes worried about not being able to breastfeed her baby. Researchers want to help the community, especially breastfeeding mothers, to consume katuk leaf stew during the current Covid-19 pandemic, considering that katuk leaves are very easy to get in the market and the price is cheap. However, previously the researcher wanted to see how much influence the katuk leaf stew had on the adequacy of breast milk. The purpose of this study was to analyze the effect of katuk leaf decoction on the adequacy of breast milk in nursing mothers during the Covid-19 pandemic. This type of research is quantitative analytic with a Quasy-Experiment research design with One Group Pretest-Posttest. The study population was all mothers who had babies aged 0-2 years at Eka Sri Wahyuni ​​Maternity Clinic. Data analysis using the Wilxocon test was used to analyze how much influence the katuk leaf decoction had on the adequacy of breast milk. The results of this study were the effectiveness of katuk leaves on breastfeeding adequacy with a P-value of 0.002.